METHODS OF TEACHING STUDENTS TO TEXT PROBLEMS AND SOLVE THEM IN PRIMARY CLASS MATHEMATICS LESSONS (Journal of Universal Science Research, 2023)
Currently, in developed countries around the world, great attention is being paid to the education of young people, and state programs on these issues are also being adopted. In this regard, fundamental reforms are being carried out in the continuous education system of Uzbekistan, and issues of intellectual level, knowledge, outlook and competitiveness of the acquired knowledge of young people are being analyzed in them. After all, "our main goal is to build a new Uzbekistan